Digital Literacy Enhancement of Rural Women in Luna, Apayao, Philippines - Jamias, Augustus Franco B.; Flor, Benjamina; Jamias, Serlie; Dizon, Josefina (Silliman Journal, 2022)
The study determined how women in Luna, Apayao who attended the digital literacy training at the Community e-Center from 2011 to 2013 applied what they learned to themselves, their families, and their communities. Data were gathered from 50 rural women from May 19 to June 1, 2014 using a self-administered questionnaire, key informant interviews, and secondary documents. The research was guided by the Technological Determinism Theory of Marshall McLuhan (1962). All of the trainees were married, with mean age of 42 years and college or postgraduate holders. Majority had jobs, mainly teachers, and were members of organizations such as the Parents–Teachers Association. To gain access to the Internet, they used portable broadband/ DSL or visited the e-Center. Half of them used the Internet for only 1 to 2 hours per week. Majority gained knowledge on ICT operations such as how to use MS Word, MS PowerPoint, Facebook, email, and MS Excel. The women gained self-confidence as this was their first exposure to ICT. The advantages to their families included facilitating academic assistance to their children and getting connected with their family members abroad, some of whom were OFWs. Lastly, they applied their training in community activities and projects, specifically in education, health and nutrition, entrepreneurship and livelihood, and safety and security. Only one mentioned agriculture, sustainable development, climate change and disaster risk management, youth empowerment, and governance.